Masters of mischief - e uthor; Russell, Nikki (New York : Aladdin, 2019)
Max and Erin continue the fight to protect South Ridge Middle School from Ralph and his henchmen, but Max's greatest challenge may be keeping his crush on Erin a secret.
4.8
3-6
640L
W
Keywords: Heroes -- Juvenile fiction; Thieves -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Humorous stories; Heroes -- Fiction; Robbers and outlaws -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Humorous stories; Humorous fiction